In the interfaces of oxygen depletion: A case study of the environmentalities of Carsten from Hjarbæk Fjord and the Danish Society for Nature Conservation in The Green Tripartite - Ambro, Asta (Culture and History: Student Research Papers, 2025)
This article explores biosocial frictions unfolding in the interfaces of oxygen depletion. The Green Tripartite (Den Grønne Trepart), a national Danish agreement aiming to reduce nitrogen, create more ‘nature’ and lower CO2, through agricultural restructuring, signals new forms of collaboration and combat. Drawing on ethnographic fieldwork and recent environmental scholarship, I analyze how Carsten, a daily visitor of Hjarbæk Fjord, and the Danish Society for Nature Conservation (Danmarks Naturfredningsforening) engage with oxygen depletion through divergent environmentalities. A central point is that these divergent ways of knowing, responding to, and being shaped by oxygen depletion reveal embodied political disagreements between urban, scientific bureaucrats and rural, anti-elitist populations, and their more-than-human relations.